Prevalence, awareness, treatment and control of dyslipidemia in older persons in urban and rural population in the Astana region, Kazakhstan - Adil Supiyev; Talgat Nurgozhin; Zhaxybay Zhumadilov; Anne Peasey; Jaroslav A. Hubacek; Martin Bobak (BMC, 2017)
Abstract Background Despite high cardiovascular mortality in Central Asian republics of the former Soviet Union, there is limited information about major risk factors, including blood lipids. We investigated the prevalence of impaired concentrations of blood lipids, the awareness, treatment and control of hypercholesterolemia, and factors associated with these indicators in urban and rural populations in Kazakhstan. Methods We conducted a cross-sectional study of random urban and rural population samples (the state capital Astana and Akmol village). Men and women aged 50-74 years were examined; a total of 954 adults participated (response rate 59%). Serum concentrations of total, LDL and HDL cholesterol and triglycerides and a range of other cardiovascular risk factors were measured. Results The overall prevalence of hypercholesterolemia (total cholesterol ≥6.2 mmol/l) was 37%; among subjects with hypercholesterolemia, 57% were aware of their condition, 41% took medication and 23% had total cholesterol <6.2 mmol/l (4.5% <5 mmol/l). The prevalence, awareness, treatment, and control of hypercholesterolemia were all higher in the urban than the rural area. Similarly, the proportions of subjects with impaired concentrations of specific lipids fractions were also considerably higher in the urban population. Most associations with other covariates were in the expected direction. Conclusions This study found relatively high prevalence of dyslipidemia in the Kazakh population, and the blood lipid profile was less favourable in the urban area. These pronounced urban-rural differences may be related to urbanization, the associated nutrition transition and to access to health care.